ntPET: A New Application of PET Imaging for Characterizing the Kinetics of Endogenous Neurotransmitter Release - Evan D. Morris; Karmen K. Yoder; Chunzhi Wang; Marc D. Normandin; Qi-Huang Zheng; Bruce Mock; F. Muzic Raymond; Janice C. Froehlich (Molecular Imaging)
We present a new application of positron emission tomography (“ntPET” or “neurotransmitter PET”) designed to recover temporal patterns of neurotransmitter release from dynamic data. Our approach employs an enhanced tracer kinetic model that describes uptake of a labeled dopamine D2/D3 receptor ligand in the presence of a time-varying rise and fall in endogenous dopamine. Data must be acquired during both baseline and stimulus (transient dopamine release) conditions. Data from a reference region in both conditions are used as an input function, which alleviates the need for any arterial blood sampling. We use simulation studies to demonstrate the ability of the method to recover the temporal characteristics of an increase in dopamine concentration that might be expected following a drug treatment. The accuracy and precision of the method—as well as its potential for false-positive responses due to noise or changes in blood flow—were examined. Finally, we applied the ntPET method to small-animal imaging data in order to produce the first noninvasive assay of the time-varying release of dopamine in the rat striatum following alcohol.